(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Rasa Shastra is the pharmaceutical branch of Ayurveda. As like any other medical system, success of Ayurvedic treatment also depends upon quality of medicine prescribed to the patient. The integral part of Rasa Shastra lies in the successful pharmaceutical process. Rasaoushadis are the potent Ayurvedic preparations mainly containing metals and minerals. These Oushadis possess wide range of therapeutic efficacy and are considered superior because of their qualities like small dose, quick action, palatability and longer shelf life. Amritamanjari is an important Rasa oushadi described in Bhaishajya Ratnavali- Amavata Adhikarana indicated in Amavata. Amritamanjari contains Suddha Hingula (Cinnabar), Suddha Vatsanabha (Aconitum ferox), Suddha Tankana (Borax), Pippali (Piper longum), Maricha (Piper nigrum) and Jatikosa (Jatiphala- Myirstica fragrans). The pharmaceutical procedures adopted in this study are Shodhana, Churnanirmana and preparation of Vati of Amritamanjari. The specific pharmaceutical blend of these contents can result in a more effective formulation. Till now, no research work has been carried out to standardize this formulation. Therefore the present study has been planned to standardize the method of preparation of Amritamanjari according to the method explained in the classical literature.